Trichothecene genotypes and chemotypes in Fusarium graminearum complex strains isolated from maize fields of northwest Argentina - Sampietro, Diego Alejandro (2012)
Members of the Fusarium graminearum species complex (Fg complex) cause Gibberella ear rot in maize from northwest Argentina. The potential of these pathogens to contaminate maize grains with type B trichothecenes is a health risk for both humans and animals. We evaluated the reliability of multiplex PCR assays based on TRI3 and TRI12 genes, and single PCR assays based on TRI7 and TRI13 genes to infer trichothecene chemotypes of 112 strains of Fg complex collected from northwest Argentina, checking trichothecene production by chemical analysis. Single and multiplex PCR assays indicated that strains belonging to F. meridionale (87/112) had a NIV genotype. The remainder strains (25/112), which belonged to F. boothii, had a DON genotype (based on single PCR assays) or 15ADON genotype (based on multiplex PCR assays). No strains tested were incorrectly diagnosed with a DON/NIV genotype. Chemical analysis indicated that the F. meridionale strains were NIV producers only (44/87), major NIV producers with unexpected high DON/NIV ratios (36/ 87), or unexpected major DON producers with minor NIV production (7/87). Strains with atypical DON/NIV production seem to be new phenotypes under a putative NIV genotype, since PCR assays do not provide evidences of a new trichothecene genotype. DON production and absence of its acetylated forms were shown for strains of F. boothii. The inconsistencies between genetic and chemical data highlight the risk of inferring the trichothecenes potentially contaminating food and feedstuffs based only on PCR assays. This study confirms for the first time that strains of Fg complex from maize of northwest Argentina are DON and NIV producers. In addition, dominance of NIV producers in the Fg complex population isolated from maize is unprecedented in Argentina, and of significant concern to food safety and animal production.